Analysing the relationship between lncRNA and protein‐coding gene and the role of lncRNA as ceRNA in pulmonary fibrosis. Issue 6 (6th April 2014) - Song, Xiaodong; Cao, Guohong; Jing, Lili; Lin, Shengcui; Wang, Xiaozhi; Zhang, Jinjin; Wang, Meirong; Liu, Weili; Lv, Changjun
Abstract Long non‐coding RNAs (lncRNAs) are involved in various pathophysiologic processes and human diseases. However, their dynamics and corresponding functions in pulmonary fibrosis remain poorly understood. In this study, portions of lncRNAs adjacent or homologous to protein‐coding genes were determined by searching the UCSC genome bioinformatics database. This was found to be potentially useful for exploring lncRNA functions in disease progression. Previous studies showed that competing endogenous RNA (ceRNA) hypothesis is another method to predict lncRNA function. However, little is known about the function of ceRNA in pulmonary fibrosis. In this study, we selected two differentially expressed lncRNAs MRAK088388 and MRAK081523 to explore their regulatory mechanisms. MRAK088388 and MRAK081523 were analysed as long‐intergenic non‐coding RNAs (lincRNAs), and identified as orthologues of mouse lncRNAs AK088388 and AK081523, respectively. qRT‐PCR and in situ hybridization (ISH) showed that they were significantly up‐regulated, and located in the cytoplasm of interstitial lung cells. We also showed that MRAK088388 and N4bp2 had the same miRNA response elements (MREs) for miR‐200, miR‐429, miR‐29, and miR‐30, whereas MRAK081523 and Plxna4 had the same MREs for miR‐218, miR‐141, miR‐98, and let‐7. Moreover, the expression levels of N4bp2 and Plxna4 significantly increased in fibrotic rats, and were highly correlated with those of MRAK088388 and MRAK081523, respectively. Among their shared miRNAs, miR‐29b‐3p and let‐7i‐5p decreased in the model group, and were negatively correlated with the expression of MRAK088388 and MRAK081523, respectively. MRAK088388 and MRAK081523 could regulate N4bp2 and Plxna4 expression by sponging miR‐29b‐3p and let‐7i‐5p, respectively, and possessed regulatory functions as ceRNAs. Thus, our study may provide insights into the functional interactions of lncRNA, miRNA and mRNA, and lead to new theories for the pathogenesis and treatment of pulmonary fibrosis.